Waste Collection and Transport Optimization of Pemalang District Service Area, Pemalang Regency - Adranandini Noor Anisa; Mochtar Hadiwidodo; Sudarno Sudarno; Sri Sumiyati (Universitas Diponegoro, 2022)
This study was prepared with the aim to plan the optimum transportation system in Pemalang sub-district based on traffic conditions in accordance with the desired target. The method used in this planning uses GIS-based applications, namely network analyst and google map. The operational cost of the vehicle in this planning is calculated by the PCI (Pacific Consultant International) method. Based on existing conditions, the operational costs of vehicles incurred reached Rp2,361,445,231.21 while in optimization conditions the operational costs incurred became more efficient at Rp2,913,093,684.31. The optimum time of transportation is done at 05.00 – 12.00 to avoid peak traffic hours at 13.00 – 17.00 with a vehicle travel speed of 47.42 km/h. Addition of freight after optimization so that it becomes 50 freight/day and the addition of containers to 9 containers. It was obtained for 2021 - 2025 as many as 17 containers as well as the addition of freight as many as 15 freight, and 6 fleets of armroll truck carriers.